2000
DOI: 10.1152/ajpregu.2000.279.1.r93
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous brain IL-1 mediates LPS-induced anorexia and hypothalamic cytokine expression

Abstract: The present study was designed to determine the role of endogenous brain interleukin (IL)-1 in the anorexic response to lipopolysaccharide (LPS). Intraperitoneal administration of LPS (5-10 microgram/mouse) induced a dramatic, but transient, decrease in food intake, associated with an enhanced expression of proinflammatory cytokine mRNA (IL-1beta, IL-6, and tumor necrosis factor-alpha) in the hypothalamus. This dose of LPS also increased plasma levels of IL-1beta. Intracerebroventricular pretreatment with IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
105
0
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(119 citation statements)
references
References 33 publications
(47 reference statements)
6
105
0
8
Order By: Relevance
“…Centrally delivered IL-1Ra abrogates these effects. 70 Together, these findings suggest that the ventricular IL-1␤ induces via IL-1R and/or AP-1, IL-1␤ and other cytokines' synthesis, a bona fide cytokines cascade. The IL-1␤ signal may also propagate by diffusion of IL-1␤ throughout the CSF.…”
Section: Il-1 and Tnf␣ In The Csfmentioning
confidence: 88%
“…Centrally delivered IL-1Ra abrogates these effects. 70 Together, these findings suggest that the ventricular IL-1␤ induces via IL-1R and/or AP-1, IL-1␤ and other cytokines' synthesis, a bona fide cytokines cascade. The IL-1␤ signal may also propagate by diffusion of IL-1␤ throughout the CSF.…”
Section: Il-1 and Tnf␣ In The Csfmentioning
confidence: 88%
“…This contrasts with LPS-induced anorexia, which is inhibited by IL-1ra (14,23). It is unlikely that the lack of effect of IL-1ra on the poly I:C-induced reduction in food intake is because of loss of activity over time, since we have previously demonstrated that a similar dose of IL-1ra inhibited the effect of the appetite suppressant leptin over a 22-h period (30).…”
Section: Discussionmentioning
confidence: 77%
“…LPS administration stimulates the release of pro-inflammatory cytokines such as IL1, TNFa, IL6, and so on (O'Reilly et al 1988, Plata-Salaman 1999, Wong & Pinkney 2004, Bennani-Baiti & Walsh 2011. These cytokines may be associated with the induction of anorexia; however, hypothalamic inflammatory signals, rather than peripheral, have been identified as the major causes of LPS-induced anorexia (Laye et al 2000, Plata-Salaman 2000, Wisse et al 2007). In line with previous studies, the mRNA levels of cytokines such as IL1a, IL1b, TNFa, and IL6 were significantly increased in the hypothalamus after LPS administration.…”
Section: Nfkb Activation In the Hypothalamus Is Involved In Lps-inducmentioning
confidence: 99%